Valid time database implementation using Oracle11g Workspace Manager - Rugtanom, Sitti; Chittayasothorn, Suphamit (My University, 2012)
Valid time database comprises valid time state tables, which keep facts that are currently true, believed to be true in the past, and expected to be true in the future. Temporal queries on these tables are both useful and necessary for many applications. However, the introduction of valid time periods to database tables leads to complex data manipulations especially delete and update operations. Conventional Database Management Systems users have to use standard SQL to handle temporal queries and temporal data manipulations which lead to long and complicated SQL statements. This paper investigates the valid time temporal database features which are available in Oracle11g. We found that the Oracle11g Workspace Manager provides valid time temporal database operations comparable to those appear in temporal database literatures.
Keywords: Oracle11g Workspace Manager; Temporal database; Valid time state table